EKSPLORASI METODE YANBU’A DALAM MENCAPAI TARGET PEMBELAJARAN - Nailah, Nailah; Odik Afifin, Muhammad (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study explores the application of the yanbu'a method in learning the Qur'an at Madin Hisbullah Khotib, focusing on its effectiveness in improving the skills of reading, writing, and memorizing the Qur'an according to the rules of tajwid. Using a qualitative approach, data were collected through interviews and observations, analyzed using data reduction techniques. The results of the study indicate that the yanbu'a method, with a systematic seven-volume structure, allows students to complete learning in an average of two years. The advantages of this method lie in the direct approach without spelling, the use of Usmani rosm, and the emphasis on makharijul huruf and tajwid, which support Qur'an literacy while deepening spiritual understanding. Supporting factors such as discipline, synergy with parents, and varied learning media strengthen its effectiveness. However, challenges such as lack of focus of students and limited facilities need to be overcome through intensification of guidance, teacher training, and technological innovation such as digital applications. The yanbu'a method has proven to be holistic, forming students who are proficient and have Islamic character, making it a relevant adaptive learning model for Islamic education.